# Re: completeness of the relational lattice

From: Jan Hidders <hidders_at_gmail.com>
Date: Tue, 26 Jun 2007 20:48:20 -0000

```>
>
> OK now you earned your notation. If you also derive (R /\ 00) \/ (R /\
> 11) = R, I would be totally sold out.

```

I hope you'll forgive me if I'm slightly skeptical about that. :-) Anyway, such a challenge I cannot refuse, of course. To be clear, I will answer the points you raised, but that requires some more thinking, because there are some deep and fundamental issues there, and that requires some more thought.

So you want me to prove, in my notation:

(R(x,y) * []) + (R(x,y) * W) = R(x,y)

(R(x,y) * []) + (R(x,y) * W)
(22) = [x,y] + (R(x,y) * W)
(9) = ([x,y] + R(x,y)) * ([x,y] + W)
(10) = R(x,y) * ([x,y] + W)
(11) = R(x,y) * (([x] * [y]) + W)
(9) = R(x,y) * (([x] + W) * ([y] + W))
(32b) = R(x,y) * <x> * <y>
(28) = R(x,y)

Remark: rule 32b is from the posting with errata for the rules for W. To repeat:

(32a) W + [] = {()}
(32b) W + [x] = <x> with x a single attribute
(32c) [H] * W = [] * W

• Jan Hidders
Received on Tue Jun 26 2007 - 22:48:20 CEST

Original text of this message